PENERAPAN LEAN MANUFACTURING DALAM PENINGKATAN PRODUKTIVITAS ALUMUNIUM BAKING TRAY - Sadiq Ardo Wibowo (Universitas Putera Batam, 2021)
Along with the rapid growth of the manufacturing industry, companies are required to create advantages in order to survive and compete with competing companies. Competition between companies requires every manufacturer to make improvements for the better. One of the industry players who are expected to make improvements is TS. aluminum. Where the improvements made focus on the production process line related to the company's productivity. The production process often arises in the form of a series of wastes such as waiting time (waiting time), work in process (WIP) and transportation that is too long. A number of these wastes can result in disruption to performance and decreased productivity. Through this research, efforts were made to reduce waste by using lean manufacturing, VSM, and FMEA. The results showed that there was a decrease in the set up time to 2135 seconds, the waiting time between cutting and filing operations to 256.8 seconds, the turning waiting time to 262.31 and the loss of transportation distance by 22 m in the finishing polishing operation which resulted in the time required reduced to 123.94 seconds. In addition, the company experienced an increase in labor productivity of 5.18, capital productivity of 28.52, productivity of raw materials 4.3, productivity of other components by 33.65 and total productivity of the company by 2.04.